Consumer attitude towards eco-friendly practices in the lodging industry in Delhi-NCR - Gupta, Ankita (IJRDO - Journal of Business Management, 2017)
This study explores the factors which inﬂuence the consumer attitude towards the environment friendly practices in the lodging industry in Delhi-NCR. It also explores the consumers’ intentions to pay for such practices. A quantitative and qualitative research methodology along with secondary research has been proposed. A structured questionnaire (from a secondary source) has been used using convenience-sampling techniques. Correlation and factor analysis has been used to look at consumers’ attitudes and behaviour towards the green practices in the lodging industry. The findings show that consumers using hotel services are conscious about environment-friendly practices. They frequently use the hotels that have adapted green practices though not compromising on service quality. The consumers would prefer to use lodging that follows these practices but are not willing to pay extra bucks for these services. Thus, the hotels would have to invest in eco-friendly practices and look at not just short-term but long-term gains. The government needs to acknowledge and institutionalise the practice by instituting rewards and offering tax and other beneﬁts. The paper tries to bring out facts regarding customer buying behaviour towards green practices in the Indian hotel industry. The resource scenario in India is dismal with regard to the water and sanitation. The tourism industry has a big responsibility in ensuring that the adopted business models are sustainable in the long run and hence the need to imbibe green practices as a preferred business model